EGFRvIII-driven microenvironmental fibroblast activation and transformation accelerate oral cancer progression via lipocalin-2/STAT3 axis - Hsuan-Yu Peng; Kwang-Yu Chang; Wei-Min Chang; Chia-Yu Wu; Hsin-Lun Lee; Yung-Chieh Chang; Ko-Jiunn Liu; Shine-Gwo Shiah; Ching-Chuan Kuo; Jang-Yang Chang (Neoplasia: An International Journal for Oncology Research)
Oral squamous cell carcinoma (OSCC) is an aggressive malignancy frequently characterized by dysregulated epidermal growth factor receptor (EGFR) signaling. Among EGFR mutation, EGFRvIII, an extracellular domain truncated form without exons 2–7, exhibits ligand-independent and constitutive EGFR activation. Although EGFRvIII functions as an oncogene in glioblastoma, its role in OSCC remains unclear. Here, we demonstrate that EGFRvIII is highly prevalent in OSCC, with approximately 70 % of OSCC tumor samples revealing high EGFRvIII expression. EGFRvIII enhances metastatic and proliferative potential, while its knockdown significantly reduces these malignant phenotypes. Beyond its direct oncogenic effects, EGFRvIII actively remodels the tumor microenvironment (TME) by recruiting and activating fibroblasts. In both xenograft models and co-culture systems, OSCC cells expressing EGFRvIII stimulated the expression of fibroblast activation markers—including α-smooth muscle actin (α-SMA), platelet-derived growth factor receptors (PDGFRA/PDGFRB), and collagen—thereby promoting a tumor-supportive stroma. Moreover, RNA sequencing and cytokine array analyses revealed that EGFRvIII induces lipocalin-2 (LCN2) expression and secretion. Elevated LCN2 in the conditioned medium from OSCC-EGFRvIII cells further stimulates fibroblast activation via the STAT3 signaling pathway, as pharmacological inhibition of STAT3 attenuates LCN2-driven fibroblast activation. Furthermore, exposure to environmental carcinogens such as nicotine-derived nitrosamine ketone (NNK) and arecoline enhances EGFRvIII expression and downstream signaling, exacerbating tumor aggressiveness. These findings reveal a positive feedback loop in which EGFRvIII fosters OSCC progression by stimulating LCN2-STAT3-mediated fibroblast activation. Targeting EGFRvIII and its downstream effectors may therefore represent a promising strategy to mitigate OSCC progression and improve therapeutic outcomes.